Technology in the Pharmacy Learning Environment: Surveys of Use and Misuse - Kimberley J. Begley; Michael S. Monaghan; Cheri W. Clavier; Ralph A. Lugo; Michael A. Crouch (University of Minnesota Libraries Publishing, 2015)
The use of technology in the classroom may have positive and negative effects on learning. The purpose of this investigation was twofold: to identify the effect technology is having on the pharmacy learning environment; and, to assess students' use of technology during class time for non-academic purposes. This study included a national cross-sectional survey as well as a single, college-specific survey. The national survey had a faculty response rate of 71.2%. Of the responders, approximately 61% identified significant problems related to students' use of technology in the pharmacy learning environment. Cell phones were a recognized concern and more than 90% of programs have chosen to restrict cell phone use in the classroom. The single college survey examining technology use during class for non-academic purposes had a student response rate of 87% and faculty response rate of 100%. Students and faculty members disagreed regarding the negative effects of technology use during class for non-academic purposes. Notably, 16% of students acknowledged their in-class use of technology for non-academic purposes had been disruptive to their learning, as compared to 95.7% of faculty. According to students, common reasons for off-task technology use included checking e-mail/text messages (75.1%), lack of engagement (58.1%), multitasking (56.2%), and accessing social media sites (33%). Faculty and students were asked about enforcement of technology policy. More faculty than students supported policy enforcement by faculty (65.2% versus 22.8%, respectively; p<0.001) as well as policy enforcement by students (78.3% versus 31.9%, respectively; p<0.001). Overall, technology use during class for non-academic purposes was common. Many schools and colleges of pharmacy are developing approaches to address these evolving issues by revising their technology use policies.   Type: Original Research